2022
DOI: 10.1002/dad2.12282
|View full text |Cite
|
Sign up to set email alerts
|

Online monitoring of financial capacity in older adults: Feasibility and initial findings

Abstract: Introduction Impairment in financial capacity places older adults at risk of fraud or abuse and can be a harbinger of loss of independence. Online automated monitoring of financial transactions offers an objective, unobtrusive, and continuous data collection strategy to minimize risk and to detect early changes in an important complex activity of daily living. Methods Ninety‐three participants used an online financial activity monitoring platform that extracted metrics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“… 29 , 30 These findings also contribute towards the body of evidence supporting the feasibility of remote neuropsychological assessments for both research and clinical assessment. 31 35 …”
Section: Discussionmentioning
confidence: 99%
“… 29 , 30 These findings also contribute towards the body of evidence supporting the feasibility of remote neuropsychological assessments for both research and clinical assessment. 31 35 …”
Section: Discussionmentioning
confidence: 99%
“…The online monitoring of financial transactions can alert users to suspicious activity and even detect a decline in financial competence. A study by Wild et al [70] found a significant negative correlation (p = 0.03) between a simplified measure of financial capacity and the number of automated alerts triggered on older adult participants' financial transactions. This expands on recent research that successfully linked the type, frequency, and duration of computer usage with mild cognitive impairment [71].…”
Section: Characterization Of Quarantine Technology Initiates and Thei...mentioning
confidence: 99%
“…An opportunity exists for new primary research that leverages the natural experiment provided by COVID-19 to identify and evaluate this vulnerable group of hesitant ICT adopters. The approaches to the mitigation of privacy risks identified in the included studies were not distinguished for QTIs from approaches for other older adults and comprised various educational strategies, automated financial transaction monitoring [70], and the application of international models, such as Europe's General Data Protection Regulation (GDPR) and the Digital Single Market (DSM) [8].…”
Section: Reflections and Contributionsmentioning
confidence: 99%